Transient response of head slider with geometry change in head surface of magnetic storage systems - Mongkolwongrojn, M.; Gunnuang, W. (My University, 2002)
In this study, the dynamic flying characteristics of the worn head sliders are investigated theoretically due to the change in head geometry caused by head and disk contact. The film shapes can be approximated as taper- Truncated cycloidal-flat film. Two-dimensional time dependent modified Reynolds equation included molecular slip effect are formulated with neglected the roughness effect. The motion of head slider was assumed to have two degree of freedom in this work. Finite difference approximation with Newton Raphson iterative technique and the fourth order Runge-Kutta method were implemented to obtain the transient response of the slider head with various change in head geometry numerically and compared with IBM3380 type head The simulation results show the film shape has affects significantly on the static and dynamic characteristic of slider head in magnetic storage systems.